Study of Physical Structure and Organization of Central Sterile Supply Department of a Tertiary care Teaching hospital - Yatoo, G H; Malhotra, Monica; Kumar, Sunil (Innovative Journal of Medical and Health Sciences, 2021)
Hospital acquired infection or “nosocomial infection” adversely affects both patients and hospitals. Impact of nosocomial infections ranges from increased length of hospital stay, emotional stress, disability, death of the patients as well as increased hospital cost for the patients and providers. Studies in India have reported nosocomial infection rates from 8% to 58 %. To combat these infections, hospital needs effective methods of disinfection and sterilization which has nowadays been centralized into a single department called Central Sterile Supply Department.